Optimization of micro propagation protocol by indirect organogenesis of Eucalyptus grandis (Revista de Ciências Agroveterinárias, 2008)
The present work had the objective of improving the micro propagation protocol by indirect organogenesis Otimização do protocolo de micropropagação por organogênese indireta de Eucalyptus grandis Optimization of micro propagation protocol by indirect organogenesis of Eucalyptus grandis Rafael Augusto Arenhart1, Gilmar Roberto Zaffari2 Recebido em 08/03/2007; aprovado em 11/07/2008. of Eucalyptus grandis. This species has high agronomic and biotechnological interest, triggering gene insertion studies to obtain better quality plants. Exogenous genes can be inserted in callus tissues that must be regenerated to obtain modified plants. Leaf explants and micro cuttings obtained from germinated seedling of E. grandis were inoculated in culture medium with different levels of growth regulators in the callus induction and bud regeneration stages. Callus induction and formation in leaf explants occurred in 100 % of samples when cultured in medium with 2,4- D and in medium with combined TDZ and ANA. The absence of Fe-EDTA did not influence the intensity of callus formation in the explants. Induction and callus formation from micro cuttings occurred in 100 % of explants when cultured in medium with TDZ alone and combined with AIA. Bud regeneration of E. grandis has been induced in the presence of BAP alone and or combined with ANA and GA3 in culture medium.
Keywords: in vitro propagation; eucalypt; callus.